Unemployment, Money Wage Rates, and Inflation - Marion, Gérald (Relations industrielles / Industrial Relations, 1969)
This article reviews "Unemployment, Money Wage Rates, and Inflation" by Georges L. Perry.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z